Stiffness analysis of a metamorphic parallel mechanism with three configurations. (December 2019) - Tian, Hai-bo; Ma, Hong-wei; Xia, Jing; Ma, Kun; Li, Zi-zhuo
Highlights: A novel metamorphic parallel mechanism for robotic legs is proposed based on an innovative rotatable-axis revolute joint. The inverse kinematic model of the new mechanism is established and the cloud picture of its workspace is obtained. Then the possible applications of the mechanism for mechanical legs is discussed. The stiffness model is formulated with the consideration of the deformation of the main components caused by the actuation and constraints. The stiffness distributions in the sub-workspace around the desired trajectory are evaluated. Abstract: Compared with series mechanisms, a parallel mechanism has the merits of high stiffness, fast response, and centralised layout of electric cylinders, which is more suitable for the mechanical leg of a rescue robot. However, it is not flexible enough to improve the environment adaptability of the robot. Adding the abilities of reconfiguration and mobility change to general parallel mechanisms, a novel metamorphic parallel mechanism for robotic legs is proposed based on an innovative rotatable-axis revolute joint. The inverse kinematic model of the new mechanism is established and the constraint conditions and ranges of the key parameters are explored, as well as obtaining the cloud picture of its workspace. The stiffness model is formulated with the consideration of the deformation of the main components caused by the actuation and constraints, utilising the screw theory. The stiffness matrices of the home positions of configurations I and III are then acquired and the stiffness distributions in the sub-workspace around the desired trajectory are evaluated, which are expected to lay a good theoretical foundation for the application of this novel mechanism.